Risk of hemorrhage in ischemic stroke and its relationship with cerebral microbleeds - MİDİ, İPEK (ELSEVIER SCIENCE BV, 2018)
Objectives: Stroke is an important public health problem in most countries. Therefore, the treatment of stroke and its complications is important. Intracerebral hemorrhage is one of the complications of ischemic stroke. This study aimed to investigate the risk of hemorrhage in patients with acute ischemic stroke and prospectively study its relationship with cerebral microbleeds (MBs) using susceptibility-weighted imaging (SWI) that is a magnetic resonance imaging (MRI) sequence. Patients and Methods: Patients with acute ischemic stroke were included. Those who underwent treatment with tissue plasminogen activator were excluded. The patients were analyzed according to their risk factors for stroke and their relationship with intracerebral hemorrhage. Results: A total of 148 patients were included. Of these, 41 (28%) had hemorrhages in the ischemic area. The mean waist circumferences, left atrium diameter, and heart rate in these patients were higher than those in patients without hemorrhage. MBs were detected in 66 patients (44.6%) using SWI, and there was no significant relationship with the presence of hemorrhage. Intracerebral hemorrhages were significantly associated with the volume and localization of infarcts. Conclusion: Intracerebral hemorrhage in patients with acute ischemic stroke within the first 7 days after stroke onset was related to their waist circumference as well as the volume and localization of the infarct. However, there was no relationship found between the risk of hemorrhage and MBs using SWI.
Keywords: Cerebral microbleeds; Hemorrhagic transformation; Ischemic stroke; SWI; BODY-MASS INDEX; INTRACRANIAL HEMORRHAGE; TRANSFORMATION; THROMBOLYSIS; DISEASE; METAANALYSIS; ATTACK